Assessment of calibration on clinical and practical supervision among dental lecturers. - Abllah, Zurainie; Yaacob, Munirah (2018)
Aim:The purpose of this assessment was to examine the variation among faculty members of Kulliyyah of Dentistry in supervising the clinical work of students. Introduction:Consistency in the evaluation of clinical decision-making is necessary for reliable assessment of student performance and effectiveness of clinical teaching. However little has been done to examine variation in dental clinical supervision. As a professional dental practitioner and lecturer, I feel this exercise is crucial as to give the best and ‘adil (justice) to students when doing assessment of work. Materials & Methods :Twenty clinical lecturers from Kulliyyah of Dentistry were given a set of criteria of rubric, and undergone twelve stations of clinical models focusing on several procedures in dentistry clinical works. The rubric and clinical models were prepared in six different groups of specialty: Periodontic, Conservative, General Dental Practitioner, Oral Surgery, Endodontic and Prosthodontic Dentistry. Lecturers go for baseline calibration and received training by 6 content experts immediately. Re-calibration was done after training. The time given for each station is 5 minutes. The rubrics consist of 57 points. The examination used dental mirror, dental probe, dental models, x-rays, copies of students’ case note and manikin. Kappa statistics were used to determine inter-examiner reliability at baseline and re-calibration. Results : For inter-examiner statistic, the baseline calibration on 20 clinical lecturers indicated an inter-rater kappa ranging from 0.05-0.5.Re-calibration on the same 20 packages after training indicated an inter-rater kappa of 0.11-0.42. Activity kappa was in the slight to moderate agreement. Performance of majority of examiners improved with time. Conclusion:The calibration of clinical lecturers should be performed regularly as it is crucial to maintain the uniformity of the examiners reliability. Furthermore the training needs to be conducted in an effective environment to improve performance. It is hoped that continuous training nurturing the “righteous individuals” which is one of the goals in Shariah principle.